2020
DOI: 10.23736/s0392-0488.18.05765-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a detergent combined with a moisturizer for the treatment of pruritus associated with xerosis in an elderly population affected by Kaposi's sarcoma

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes. Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Tourlaki et al assessed the effect of using a detergent containing dihydroavenanthramide D 5% + 1% menthol moisturizer daily. They found that the intervention improved chronic pruritus associated with xerosis in elderly adults with Kaposi's sarcoma (Tourlaki et al, 2020).…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Tourlaki et al assessed the effect of using a detergent containing dihydroavenanthramide D 5% + 1% menthol moisturizer daily. They found that the intervention improved chronic pruritus associated with xerosis in elderly adults with Kaposi's sarcoma (Tourlaki et al, 2020).…”
Section: Clinical Applicationmentioning
confidence: 99%
“…In the elderly, Kaposi sarcoma can be fatal; according to the stage and clinical presentation, the treatment consists in a combination of chemotherapy and radiotherapy. Xerosis is a common clinical finding in this population (24,29).…”
Section: Medical Literaturementioning
confidence: 82%
“…In addition, between 2000 and 2008, the usage of antiretrovirals among the U.S. population increased (26,27).…”
Section: Medical Literaturementioning
confidence: 99%
“…Eine In der topischen Therapie hat bereits die wirkstofffreie Basistherapie mit Emollientien einen hohen Stellenwert, denn die Hydratisierung und Stabilisierung der physiologischen Hautbarriere kann den mit trockener Haut assoziierten Pruritus effizient lindern (Izumi et al 2017;Tourlaki et al 2020).…”
Section: Therapeutische Optionenunclassified